Nanoparticles of N-Vinylpyrrolidone Amphiphilic Copolymers and Pheophorbide a as Promising Photosensitizers for Photodynamic Therapy: Design, Properties and In Vitro Phototoxic Activity - Alexander Yu. Rybkin; Svetlana V. Kurmaz; Elizaveta A. Urakova; Natalia V. Filatova; Lev R. Sizov; Alexey V. Kozlov; Mikhail O. Koifman; Nikolai S. Goryachev (MDPI AG, 2023)
A series of nanoparticles (NPs) with a hydrodynamic radius from 20 to 100 nm in PBS was developed over the solubilization of hydrophobic dye methyl pheophorbide a (chlorin e6 derivative) by amphiphilic copolymers of N-vinylpyrrolidone with (di)methacrylates. Photophysical properties and biological activity of the NPs aqueous solution were studied. It was found that the dye encapsulated in the copolymers is in an aggregated state. However, its aggregation degree decreases sharply, and singlet oxygen quantum yield and the fluorescence signal increase upon the interaction of these NPs with model biological membranes-liposomes or components of a tissue homogenate. The phototoxic effect of NPs in HeLa cells exceeds by 1.5-2 times that of the reference dye chlorin e6 trisodium salt-one of the most effective photosensitizers used in clinical practice. It could be explained by the effective release of the hydrophobic photosensitizer from the NPs into biological structures. The demonstrated approach can be used not only for the encapsulation of hydrophobic photosensitizers for PDT but also for other drugs, and N-vinylpyrrolidone amphiphilic copolymers show promising potential as a modern platform for the design of targeted delivery vehicles.